A 'Brooding Oppressive Shadow'? The Labour Alliance, the 'Trade Union Question', and the Trajectory of Revisionist Social Democracy, c. 1969–1975. Issue 3 (December 2017) - Meredith, Stephen
Abstract : Conventional accounts of the decision of a group of influential British Labour MPs to leave the party in 1981 to found the new Social Democratic Party (SDP) focus on more immediate intra-party constitutional reforms after 1979, or on party divisions over the single question of Britain's membership of the European Economic Community (EEC). This article suggests that a wider array of longer-term factors informed the decision to seek an alternative vehicle of social democracy, particularly the critical response to the so-called 'trade union question' in British and Labour politics from the late 1960s in a wider 'post-revisionist' critique of traditional social democracy. It identifies the centrality and cumulative role of a new 'post-revisionist' social democratic critique of the privileged position and influence of an increasingly assertive (left-wing) trade unionism after the failure of Labour's In Place of Strife legislation in 1969 in the later schism of British social democracy.